2017
DOI: 10.4172/2329-6798.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Techniques of Micro/Nano Fibres based Nonwoven Composites: A Review

Abstract: Recently, nonwoven composites have been recognized to exhibit significant potential in several applications such as filtration, wound care, and biomedical devices. This is due to the fact that high performance nonwoven composites can be easily fabricated using cost effective as well as eco-friendly techniques. This review article presents the recent progress in fabrication techniques used for production of nonwoven composites using natural and synthetic polymers for textile application in particular. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[78] Nonwoven textile is widely used in the fields of medical protective clothing, blankets, garments, air filters, packaging, automobiles, geotextiles, drapes, wound dressing, crop covers, masks, and wet tissues as a result of the advantages of light weight, high output, moderate strength and stability, good stability, and low cost. [79][80][81] Nonwoven textile can be divided into melt-blown, needlepunched, spun-bonded, spun-laced, and thermal-bonded nonwoven textile according to the difference in the fabrication method and process. [82][83][84][85] There are a variety of polymers that can be used to manufacture nonwoven textile, such as polypropylene (PP), polyester (PET), polylactic acid (PLA), polyamide (PA), and so on.…”
Section: Preparation Methods Of Nonwoven Textile With Polymeric Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…[78] Nonwoven textile is widely used in the fields of medical protective clothing, blankets, garments, air filters, packaging, automobiles, geotextiles, drapes, wound dressing, crop covers, masks, and wet tissues as a result of the advantages of light weight, high output, moderate strength and stability, good stability, and low cost. [79][80][81] Nonwoven textile can be divided into melt-blown, needlepunched, spun-bonded, spun-laced, and thermal-bonded nonwoven textile according to the difference in the fabrication method and process. [82][83][84][85] There are a variety of polymers that can be used to manufacture nonwoven textile, such as polypropylene (PP), polyester (PET), polylactic acid (PLA), polyamide (PA), and so on.…”
Section: Preparation Methods Of Nonwoven Textile With Polymeric Fibersmentioning
confidence: 99%
“…[81] Spun-bonded PET nonwoven textile has various excellent properties, such as dimensional stability, high strength, high elasticity, and UV resistance. [87][88][89] In addition, the needle-punched nonwoven textile has become popular due to the diverse mechanical and physical properties that can provide different thickness and densities to meet various requirements. [90,91] The short fibers are opened, carded, and laid into a web structure, and then reinforced by using needle with barbs repeatedly punching to form needle-punched nonwoven textile.…”
Section: Preparation Methods Of Nonwoven Textile With Polymeric Fibersmentioning
confidence: 99%
“…Recycled carbon fiber (rCF) generally requires further processing into textile preforms for reuse in the composites industry. The use of nonwoven preforms is attractive due to their high production rates, greater than an order of magnitude faster than woven textiles [15]. The high value placed on low cost and rapid processing by the automotive industry makes nonwoven textiles a natural fit for automotive composite reinforcement.…”
Section: Textiles Manufactured Using Recycled Carbon Fibersmentioning
confidence: 99%
“…With the addition of filler and in-line impregnation, manufacturers can control the material functionality and explore various potential applications ranging from filtering to roofing substrates to semi-structural composites. Production rates vary based on several factors but have been reported at up to 1000 m per minute [15]. Ahrens [18] demonstrated that the wet-laid system allows great flexibility in the blending of different kinds of fibers.…”
Section: Wet-laidmentioning
confidence: 99%
“…Nonwoven fabrics are manufactured from directionally or randomly oriented staple fibers or endless fibers via dry-/wet-laid or melt-spinning, respectively. To provide a mechanical integrity to the web, the fibers are bonded/entangled together mechanically, thermally or chemically [6]. Nonwovens offer an extended inner surface area in the form of a 3D network of fibers and the properties of textiles can be engineered to meet specific functions in the automotive industry, medical apparel [7], and filter media [8,9].…”
Section: Introductionmentioning
confidence: 99%